HUBUNGAN SELF EFFICACY DENGAN KEMATANGAN KARIER PESERTA DIDIK KELAS XII SMA - Aan Aminah; Teti Sobari; Siti Fatimah (IKIP Siliwangi, 2021)
The purpose of this study is to study whether there is a relationship between self-efficacy and career maturity of class XII SMA Asshiddiqiyah infuture career decision-making activities. The research method used is quantitative ex post facto correlations with variables that can affect self-efficacy and independent variables career maturity. The research sample involved was 72 students of class XII SMA Asshiddiqiyah. Data analysistechniques using product moment correlation. Based on the hypothesis testing the relationship between self-efficacy with observability, students'training results are obtained, there is a positive relationship between self-efficacy and career progression. The positive relationship between self-efficacy and career relations is at a moderate level of correlation with a correlation coefficient of 0.425.Keywords: self-efficacy, career maturity.